African reaction to white penetration: The Hananwa of Blouberg, ca. 1886-1894 (Historia, 2021)
This article focuses on the interaction between an African community of the northern Soutpansberg District and the officials of the Transvaal Government during the last decade of the nineteenth century. The reaction of the Hananwa of Blouberg to the Pretoria Government's measures to turn them into Boer subjects through the appropriation of their land, labour and taxes, is considered and compared with the reaction of the Africans in the central parts of the Transvaal almost a decade and a half earlier. Unlike the situation in the more densely (white) populated central parts of the Transvaal, white demands for African land and labour were not among the primary causes of conflict between the Boers and the Hananwa. Their reluctance to pay taxes and the activities of the local Native Commissioner, ultimately led to the Boer-Hananwa War of 1894
Keywords: African land; African communities; Hananwa of Blouberg; Boer subjects; White penetration; South African Republic; White interference; History